Self-Supported Biopolymeric Films Based on Onion Bulb (Allium cepa L.): Gamma-Radiation Effects in Sterilizing Doses - da Costa Borges, Marco Antonio; Sorigotti, Amanda Rinaldi; Paschoalin, Rafaella Takehara; Júnior, José Alberto Paris; da Silva, Lucas Henrique Domingos; Dias, Diógenes Santos; Ribeiro, Clóvis Augusto [UNESP]; de Araújo, Elmo Silvano; Resende, Flávia Aparecida; da Silva Barud, Hernane (MDPI, 2023)
Sterilization is a fundamental step to eliminate microorganisms prior to the application of products, especially in the food and medical industries. γ-irradiation is one of the most recommended and effective methods used for sterilization, but its effect on the properties and performance of bio-based polymers is negligible. This work is aimed at evaluating the influence of γ-radiation at doses of 5, 10, 15, 25, 30, and 40 kGy on the morphology, properties, and performance of bioplastic produced from onion bulb (Allium cepa L.), using two hydrothermal synthesis procedures. These procedures differ in whether the product is washed or not after bioplastic synthesis, and are referred to as the unwashed hydrothermally treated pulp (HTP) and washed hydrothermally treated pulp (W-HTP). The morphological analysis indicated that the film surfaces became progressively rougher and more irregular for doses above 25 kGy, which increases their hydrophobicity, especially for the W-HTP samples. In addition, the FTIR and XRD results indicated that irradiation changed the structural and chemical groups of the samples. There was an increase in the crystallinity index and a predominance of the interaction of radiation with the hydroxyl groups—more susceptible to the oxidative effect—besides the cleavage of chemical bonds depending on the γ-radiation dose. The presence of soluble carbohydrates influenced the mechanical behavior of the samples, in which HTP is more ductile than W-HTP, but γ-radiation did not cause a change in mechanical properties proportionally to the dose. For W-HTP, films there was no mutagenicity or cytotoxicity—even after γ-irradiation at higher doses. In conclusion, the properties of onion-based films varied significantly with the γ-radiation dose. The films were also affected differently by radiation, depending on their chemical composition and the change induced by washing, which influences their use in food packaging or biomedical devices.
Keywords: casting; effect of washing; onion-based films; sterilization; γ-radiation